Mean Mesiodistal Width Determination of Canines in Patients Reporting to a Tertiary Care Hospital at Karachi - Muhammad Ashfaq; Syed Shah Faisal; Sadia Rizwan; Syed Sheeraz Hussain (KARACHI MEDICAL AND DENTAL COLLEGE, 2020)
Objective: Objective of our study was determination of mean mesiodistal width of maxillary and mandibular canines in males and females in Pakistani population for ideal replacement of these teeth. Methods: It was a cross sectional study. Data was obtained from patients referring to orthodontic department at a tertiary care hospital. Informed consent was taken verbally from the patients recruited for study. Sample size was 130. Patients with both genders and having age range of 17-21 were included. Patients having unerupted, partially erupted, any prosthetic replacement, any restoration of maxillary or mandibular canines were excluded from the study. Mesiodistal measurement of both the upper and lower canines were obtained on the plaster casts with the help of digital Vernier caliper. All the measurements were noted on a preformed proforma (Annex-1). Results: They were 130 patients who were recruited for the study. The mean age of the patients in this study was 18.90 ± 1.523 years. Mean maxillary canine width mesiodistally was found to be 8.502 mm with standard deviation of 0.615 mm. Mean width of mandibular canine mesiodistally was found to be 7.44 mm with having standard deviation of 0.764 mm. Conclusions: This study helped us to conclude that the canines for right and left side were not exactly similar to each other. It was found that sexual dimorphism is present in the widths of maxillary and mandibular canines mesiodistally. It is also concluded from the study that males have greater mesiodistal widths of canines than females